2006
DOI: 10.1063/1.2211299
|View full text |Cite
|
Sign up to set email alerts
|

Concentration evaluation method using broadband absorption spectroscopy for sulfur dioxide monitoring

Abstract: We report on an approach for sulfur dioxide monitoring using broadband absorption spectroscopy in the ultraviolet spectral range. The method was applied in real-time measurements and has the advantage of straightforward data evaluation, limited susceptibility for interference from other gases, and low degree of complexity compared with other real-time optical detection techniques having the same precision. Concentration measurement is demonstrated at atmospheric pressure, which is of interest for pollution emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…The extrapolated minimum detectable concentration of the instrument was previously estimated to ϳ1 ppm. 15 A measurement campaign was carried out in early Spring 2006 in Harbin, China. The sensor was then tested for measurement of the SO 2 in flue gas emitted from an industrial coal-fired boiler.…”
Section: Measurement Evaluation and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extrapolated minimum detectable concentration of the instrument was previously estimated to ϳ1 ppm. 15 A measurement campaign was carried out in early Spring 2006 in Harbin, China. The sensor was then tested for measurement of the SO 2 in flue gas emitted from an industrial coal-fired boiler.…”
Section: Measurement Evaluation and Resultsmentioning
confidence: 99%
“…15 Laboratory tests on static and flowing gas displayed a measurement precision of 4% and long-term reproducibility under varying pressure and temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported measurements of H 2 S, SO 2 and/or NO 2 using broadband absorption spectroscopy techniques in the ultraviolet region performed at atmospheric pressure [18][19][20][21][22]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…However, the NO concentration measurements are hampered by the influence of SO 2 on the absorption spectrum. Sensors based on differential absorption spectroscopy in the ultraviolet (UV) wavelength region have previously been described, but the technique is grossly affected by the variation in the reference light intensity [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%